CONTRIBUTING FACTORS TO EFL STUDENTS’ SPEAKING ANXIETY - Muhamad Taufik Hidayat (Institut Pendidikan Indonesia Garut, 2021)
Anxiety is one of the most influential factors on students’ learning, especially speaking. English speaking is a language skill that is highly affected by anxiety. Therefore it suggested that the cause of this anxiety be explored to reduce its significant effect on learner. This research aimed at describing contributing factors to EFL students’ speaking. Qualitative inquiry was used as the main framework in completing the analysis. The participants of this research was EFL learners enrolled in English department in a private university in Garut. They were involved based on volunteer participation. Their identity was presented as pseudonym in order to comply with the research ethical conduct. The interviews were used to explore many contributing factors to speaking anxiety experienced by EFL Learners. The result revealed that there are nine dominant factors identified as the cause of students’ speaking anxiety, they are: cognitive and linguistic factors related to classroom procedure, strict and formal classroom environment, classroom presentation, fear of making mistakes and apprehension about others’ evaluation, role of language instructors, linguistic difficulties, pronunciation, grammar, and vocabulary